Controlling Factors of Organic Matter Enrichment in Marine–Continental Transitional Shale: A Case Study of the Upper Permian Longtan Formation, Northern Guizhou, China - Zhang, Manting; Hu, Mingyi; Cai, Quansheng; Deng, Qingjie; Wei, Sile; Wang, Kai; Li, Yuqian; Han, Ye (Minerals (Basel), 2024)
The marine–continental transitional shale of the Upper Permian Longtan Formation in northern Guizhou is an important source rock in the upper Yangtze region of China, and it holds significant potential for the exploration of shale gas. To investigate the correlation between sedimentary conditions and the accumulation of organic matters in marine–continental transitional shale, this paper performed an extensive analysis using organic geochemical testing, organic petrology examination, a cross-section polisher–scanning electron microscope (CP-SEM), and geochemical analysis. The Jinsha and Dafang drilling cores were selected as the research subjects. The results showed that the TOC of the Longtan Formation in the study area was relatively high, and the TOC content of the tidal flat–lagoon environment (average of 8.37%) was significantly higher than that of the delta samples (average of 2.77%). The high content of Al2O3 (average of 17.41% in DC-1, average of 16.53% in JC-1) indicated strong terrigenous detrital input. The proxies indicated that the Longtan Formation shale in northern Guizhou was deposited in a climate that was both warm and humid, with oxic–dysoxic sedimentary water characterized by high biological productivity and a rapid sedimentation rate. The organic-rich shales during the marine and continental transitional phases were affected by various factors, including the paleo-climate, water redox properties, paleo-productivity, sedimentation rate, and other variables, which directly or indirectly impacted the availability, burial, and preservation of organic matter.